Europe, epicenter of the COVID-19 pandemic. Democracy and the Therapeutic State - Campani, Giovanna (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
The paper discusses the measures that have been taken by the European governments in front of the COVID-19 epidemics, raising the issues of the fundamental liberties and the state of law in front of a dominating right to health. Exploring the differences among the lockdown measures – more draconian – Chinese style – as Italy or Spain – or softer as Germany and Northern European countries, the article considers as well the positions of philosophers as Giorgio Agamben or Bernard-Henri Lévy, and jurists, constitutionalists, lawyers. The already ancient debate about medical power in society is also evoked (Thomas Szasz). Finally, the Swedish model is evoked, together with the reactions against lockdowns by the populations, indicating that the draconian lockdown – given the damages inflicted to economy and social life – won’t be a model to follow in the future, while more balanced forms of control of the epidemic (more testing, isolation of the clusters, better reception services in the hospital) will represent the democratic answer to the challenge.